Eksplorasi Kebutuhan Pengembangan Bahan Ajar Menulis Deskriptif Berbasis Kearifan Lokal melalui Strategi Fishbone - Charlina; Elvrin Septyanti; Tria Putri Mustika (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This study explores the need for teaching materials to write descriptive texts based on local wisdom through the Fishbone strategy. The method used is ex post facto with Miles & Huberman analysis techniques and data collection techniques through questionnaires. The results of the material analysis, the average value was 3.57 with 71% with three indicators (1) analysis of learning strategy needs on the material averaged 3.52 to 70%, (2) analysis of the need for completeness of teaching materials 3.59 with 71%, and (3) analysis of the need for language rules on the material the average value is 3.69 with 73%. Then for the teaching material analysis, the average value is 3.40 with 68% with four indicators (1) analysis of the needs of learning strategies in teaching material with an average value of 3.10 with 62%, (2) analysis of the need for availability of teaching material with an average value of 3.41 with 68%, (3) analysis of the need for language principles in teaching material the average value is 3.55 with 71%, and (4) analysis of needs for evaluation of teaching material is 3.53 to 70%. It is categorized as useful but needs to be redeveloped through a fishbone strategy for maximum results to achieve an excellent category in teaching material innovation.